Family Group Conferencing with Children and Young People Advocacy Approaches, Variations and Impacts - Fox, Darrell (Springer International Publishing, 2018)
Family Group Conferences are seen as a progressive and influential form of practice in child welfare across the globe. This book examines and identifies variations in independent advocacy provision offered to young people and their families in relation to undertaking a FGC, and discusses how these can impact the outcomes both positively and negatively for young people involved. Using critical discourse analysis and an original theoretical framework, the outcomes of advocacy provision are examined from participants' perspectives prior to, during, and after the FGC process has been completed. The analysis develops themes that are discussed comprehensively and recommendations are made for the enhancement of advocacy provision generally, and, for young people involved in FGC specifically. .